Hubungan antara wilayah kendali dan tanggung jawab personal dengan intensi pro lingkungan - Dasi, Ahsanul Akhsan; Miarsyah, Mieke; Rusdi, Rusdi (Konsorsium Psikologi Ilmiah Nusantara, 2019)
Locus of control is a belief in oneself as a center of control that directs a person's behavior to move within him towards the outside of them. Personal responsibility can be defined as individuals who deal with actions that will affect others. The role of personal responsibility is important to change students' pro-environmental intention. This study aims to analyze the relationship between locus of control and personal responsibility with pro-environmental intention at SMAN 8 Makassar City. Participants for the study were 120 students from 11th grade. This study used a quantitative approach with a descriptive method of correlation techniques, using survey data. The results showed a positive relationship between locus of control and personal responsibility with pro-environmental intention.